Maru Batting Center : customer lifetime value - Hennessy, Julie, (SAGE knowledge. Cases., 2016)
This exercise is one in a series intended to help students learn how to perform financial calculations in marketing contexts. Maru Keitou, a decorated former collegiate softball player with a PhD from Oxford University, ran Maru Batting Center in the Roppongi district of Tokyo's Minato ward. She had a deep knowledge of the game and of her customers, but she lacked a marketing background. She had recently signed up for a hosted customer relationship management service that would allow her to track the cost of acquiring and serving each of her four main customer segments. Using this data, she could determine which segments to target in the upcoming year.